The Effect of Basic Life Support Training on Nurses' Ability to Perform Cardiopulmonary Resuscitation in the Emergency Department - Mahoklory, Serly Sani; Fitriani.K, Fitriani.K; Ibrahim, Sultan Akbar (International Journal of Health Sciences, 2025)
Background: Cardiopulmonary resuscitation (CPR) is a crucial step in treating cardiac arrest. Emergency nurses' ability to perform CPR is greatly influenced by the knowledge and skills gained from Basic Life Support (BLS) training. Objective: This study aims to analyze the effect of BHD training on nurses' ability to perform CPR in the Emergency Department (IGD). Method: Quantitative research with pre-experimental design one group pretest-posttest Design. A sample of 30 emergency room nurses was selected using total sampling. The instruments consisted of a knowledge questionnaire, a skills observation sheet, and a CPR implementation guide according to American Heart Association standards. Association (AHA) 2020. Data analysis using paired t- test with α=0.05. Results: The study showed a significant increase in nurses' abilities after receiving BHD training. The average knowledge score increased from 65.3 to 87.6, while the average skill score increased from 60.1 to 89.2 (p=0.000). Conclusion: BHD training has a significant effect on improving nurses' ability to perform CPR in the ER.